Wire arranging tool for electronic element processing - JIANG ZHIHANG (2022)
The utility model relates to the technical field of wire arrangement tools for electronic elements, in particular to a wire arrangement tool for processing electronic elements, and solves the problems of low efficiency and high possibility of errors caused by manual wire arrangement of the electronic elements in the prior art. A wire arrangement tool for electronic element processing comprises a base, the base is provided with a plurality of placing boxes used for placing electronic elements, side plates are symmetrically installed on the two sides of the base, and a wire distribution plate is vertically arranged between the two side plates in a sliding and limiting mode. According to the wire arrangement auxiliary device, the advantages of the risk board and the minute hand are utilized, simultaneous wire arrangement operation of a plurality of electronic elements is achieved, the horizontal distance and the vertical distance between a plurality of leads are all increased by the distributor board, so that wo